Aprendendo a ser político: uma abordagem experiencial - Dantas, Severino Ranielson Cunha (2021)
This study aimed to understand how individuals learn to be politicians from an experiential approach. The achievement of the objective was possible through the following specific objectives: to characterize the experiences experienced by politicians in their life trajectory; identify the contribution of experiences lived in the process of learning politicians; establish links between the experiences experienced and the learning of politicians. The theoretical foundation addressed theories of leadership, political leadership, and experiential learning. The research was conducted through a qualitative approach, and used the narrative method, specifically Oral History. Eight political leaders elected in the 2020 election for municipal executive office participated in the survey. Data were collected through semi-structured interviews. Data analysis followed the steps of comprehensive interpretative analysis. Three themes emerged, revealing categories of meanings, which helped to understand the phenomenon. The results allowed the characterization of the trajectories of political leaders reporting their experiences throughout their lives, evidencing contextual similarities and insertion in politics through family history and participation in local political groups. In addition, leadership behaviors were observed in early stages in the interviewees' lives, which served them as motivation for entering politics. Moreover, other reasons for following the political career have been the continuation of the family legacy and the possibility of contributing to the municipality they represent. The factors that limited entry into political life involve individual (skills and competencies) and contextual aspects (failures, gender barriers). The main meanings of political leadership involve representation, influence, collective thinking and profession. The essential attributes for the performance of a political leadership were identified: knowing how to relate in society (being an example, having persuasion capacity, articulating good political relations), communicating satisfactorily (communication, articulation) and having management capacity (resource management, decision making). The experiences of political leaders originate from three fields: professional experiences, formal and social education. With regard to the learning process of politicians, it was found that it occurred through the occurrence of experiences at three levels: a)the experiences acquired by professional practice enabled the development of skills that were useful to them in their political performance; b) formal education, which proved to be significant for the development of leadership by participating in complementary activities such as: student, extension and sports practice associations; c) social experiences, mediated by the family context with political history, which exerted a strong influence on the inclination towards political activity, as well as participation in religious groups and associations for the development of leadership aspects. The results contributed to broaden the conception of how political leaders experience and give meaning to their experiences on political practice.